Novel Aspects of Nitrate Regulation in Arabidopsis - Fan, Hongmei; Quan, Shuxuan; Qi, Shengdong; Xu, Na; Wang, Yong (Frontiers in Plant Science, 2020)
Nitrogen (N) is one of the most essential macronutrients for plant growth and development. Nitrate (NO3-), the major form of N that plants uptake from the soil, acts as an important signaling molecule in addition to its nutritional function. Over the past decade, significant progress has been made in identifying new components involved in NO3- regulation and starting to unravel the NO3- regulatory network. Great reviews have been made recently by scientists on the key regulators in NO3- signaling, NO3- effects on plant development, and its crosstalk with phosphorus (P), potassium (K), hormones, and calcium signaling. However, several novel aspects of NO3- regulation have not been previously reviewed in detail. Here, we mainly focused on the recent advances of post-transcriptional regulation and non-coding RNA (ncRNAs) in NO3- signaling, and NO3- regulation on leaf senescence and the circadian clock. It will help us to extend the general picture of NO3- regulation and provide a basis for further exploration of NO3- regulatory network.